The Influence of Work Environment, Organizational Culture, and Motivation on the Performance of Soldiers Yonarmed 7/105 GS - Nanang Aditya; Rini Mulyani Sari (Komando (Kompetensi Manajemen dan Organisasi): Bisnis dan Pertahanan, 2024)
The Indonesian Army receives assistance from the Combat Assistance Unit, specifically Yonarmed 7/105 GS, which is a battalion established in alignment with the Army's objective for force development. The issue of inadequate improvement in soldiers' performance at Yonarmed 7/105 GS is a result of the excessive utilization of stability and operational preparation values of Yonarmed 7/105 GS, which fall under the Steady III category. This study aims to examine the influence of the work environment, organizational culture, and work motivation on the performance of Yonarmed Soldiers 7/105 GS Bekasi. Adopting a quantitative research approach, the study focuses on the population of Yonarmed Soldiers 7/105 GS. The sample comprises 90 individuals from Yonarmed Soldiers 7/105 GS, selected through a simple random sampling technique. The study's findings indicate that the factors of work environment, organizational culture, and work motivation exert a favorable and noteworthy impact on the performance of Yonarmed Soldiers 7/105 GS Bekasi. Therefore, enhancing the work environment, implementing a successful organizational culture, and providing motivation would directly influence the performance of Yonarmed 7/105 GS Soldiers.